Black Holes on MR Images of the Brain of Patients with Björk-Shiley Heart Valves: Additional Observation in Three Cases - van Gorp, Maarten J.; de Mol, Bas A.J.M.; Bakker, Chris J.G.; van der Graaf, Yolanda; Mali, Willem P.T.M. (American Journal of Neuroradiology, 2003)
Summary: We report the cases of three patients with Björk-Shiley convexo-concave heart valves with unusual black holes shown on cerebral MR images. For two patients, these findings were associated with fracture of the Björk-Shiley convexo-concave heart valve, and for the third, with worn surfaces on the heart valve. Susceptibility changes shown by MR imaging suggest the possibility that these black holes may be associated with microscopic metallic particles, although, the exact cause of these black holes remains undetermined.